Potassium acrylate to reduce water use in greenhouse tomato cultivation - García-Moreno, Alicia; Cano-Ríos, Pedro; Quiroga-Garza, Héctor Mario; Espinoza-Arellano, José de Jesús; Muñoz-Soto, Rubi; Reyes-Carrillo, Reyes-Carrillo (Revista Mexicana de Ciencias Agrícolas, 2024)
Hydrogels are materials that absorb large amounts of water and have been used for horticultural purposes. This work aimed to make a technical and economic assessment of the use of potassium acrylate (PA) hydrogel to reduce water consumption in tomato cultivation by using three doses of PA (0, 3 and 6 g L-1 substrate), two substrates (sand and mixture: 50% sand - 40% compost - 10% perlite) and two varieties (Aquiles and Moctezuma). The experimental work was carried out in one of the greenhouses of the Antonio Narro Autonomous Agrarian University, Laguna Unit, in the city of Torreón, Coahuila, Mexico, during the spring-summer cycle of 2020. The experimental design was in randomized blocks, 12 treatments and four repetitions. The variables evaluated were: plant height, stem thickness, polar and equatorial diameter of the fruit, pulp thickness, number of locules, degrees Brix, yield, and water footprint. The economic analysis was based on the partial budget methodology proposed by the International Maize and Wheat Center for the analysis of experiments. No statistical differences were found in fruit quality. Yield increased with PA and the water footprint decreased. Marginal income (MgI) exceeded marginal cost (MgC) in the two doses of PA analyzed. PA saved water (20.1% and 21.1%) when incorporated into the substrate mixture, increased yield (25.1 t ha-1), improved income (MgI>MgC) and maintained fruit quality.